GerminaR: an R package for germination analysis with the interactive web application "GerminaQuant for R" - Lozano Isla, F.; Benites Alfaro, Omar Eduardo; Pompelli, M.F. (Wiley, 2019)
The germination process is one of the most sensitive stages in the early development of plants. The behavior and the responses of the plants in agronomic, biological and ecophysiological studies can be inferred through this process. However, the calculation of the germination variables is laborious. In this sense, the GerminaR package for the statistical software application R, which includes an interactive web application GerminaQuant for R for users without programming knowledge is presented. These tools should contribute greatly to improve analyses in germination studies.